The Broadband low-frequency sound absorption via a hexagonal acoustic metamaterial in the honeycomb structure - Fatma Nafaa (Kuwait Journal of Science)
We proposed a low-frequency absorber comprised of a hexagonal honeycomb structure is presented and demonstrated. The acoustic metamaterial of the hexagonal honeycomb structure with different folding numbers n is investigated via finite element simulations to solve COMSOL multi-physics commercial software. This technique is design to expose the influence of thickness and eccentric hexagonal designs to improve acoustic performance. A hexagonal honeycomb structure made of a soft polymer is constructed. The effect of the folding number on the absorption peak is studied, and the results indicate that a more significant folding number can dramatically increase the absorption peak frequency with the absorber decreasing thickness. The impact of structural parameters for honeycomb structure designs is demonstrated to produce a low-frequency sound absorber. To achieve unitary sound absorption at low frequencies results via adjusting the inner and outer thicknesses with the folding number n. we show influenced the hexagonal folding number and adjusting the internal  parameters of the acoustic metamaterial to paving the path for creating an ideal sound absorber